Human Resource Management Practices and Employee Engagement: An Empirical Evidence from Nepalese Commercial Banks - Kharel, Shreekrishna; Niraula, Ganesh Prasad (International Research Journal of MMC, 2026)
This study investigates the relationships between human resource management practices and employee engagement in the Nepalese commercial banks in year 2025-2026. Grounded in Social Exchange Theory (SET), the research posits that when organizations provide developmental opportunities, fair performance systems, and satisfying work conditions, employees perceive these practices as organizational support and reciprocate with higher engagement. We employed cross-sectional research design and survey data that were collected from 281 employees across the banks’ branches of the Nepalese commercial banks using a structured questionnaire. Statistical analyses were conducted through Statistical Package for Social Science (SPSS), employing correlation and regression techniques to examine the hypothesized relationships. The findings reveal that there is a positive relationship between training and development and employee engagement (0.731), there is a positive relationship between career development and employee engagement (0.736), there is a positive relationship between performance management and employee engagement (0.681), and there is a positive relationship between job security and employee engagement (0.687). Supporting the SET perspective that reciprocal exchanges foster stronger organizational commitment and discretionary effort. The study contributes to the literature by contextualizing human resource management practices within a South Asian banking sector and offers practical implications for managers seeking to enhance engagement through strategic human resource interventions.